A1.77 Interferon regulatory factor 5 (IRF5) gene variant RS2004640 is associated with carotid intima media thickness in rheumatoid arthritis patients. (31st January 2014) - Vosslamber, S; van Sijl, A; Bos, C L; Lubbers, J; de Ridder, S; Voskuyl, A E; Nurmohamed, M T; Verweij, C L
Abstract : Background and Objectives: Rheumatoid arthritis (RA) is a chronic inflammatory joint disease and is associated with an increased cardiovascular (CV) risk. Interferons (IFNs), especially IFNβ, might play a role in atherosclerosis as they are known inhibitors of vascular smooth muscle cell proliferation and intimal hyperplasia. We studied whether functional relevant SNPs in the interferon regulatory factor 5 ( IRF5) gene are associated with carotid intima media thickness (cIMT), a surrogate maker for CV disease. Materials and Methods: In 353 RA patients of the CARRÉ study, IRF5 SNPs rs2004640 and rs4728142 were determined using Taqman Genotyping assay. cIMT was determined in a subgroup of 101 patients by B-mode ultrasonography. Linear regression analyses were used to investigate the association between cIMT and IRF5 genotypes, adjusting for demographic and cardiovascular risk factors. Results: Patients homozygous for rs2004640 G-allele have higher cIMT compared to those homozygote for the T-allele (p = 0.019) and a trend towards a higher cIMT was observed (p = 0.103) for patients homozygous for the rs4728142 G-allele versus patients with the AA-genotype. Age was an effect-modifier for this association. Linear regression analysis in patients older than 60 years showed that the rs2004640 GG-genotype was associated with higher cIMT (regression coefficient 0.107 (C. I. 0.008; 0.205), p = 0.035) compared to the TT-genotype. This remained significant after adjustment for traditional risk factors (regression coefficient 0.111 (C. I.0.02; 0.202), p = 0.020). Conclusion: We demonstrate that the IRF5 gene variant rs2004640 is associated with preclinical atherosclerosis in RA patients, independent of traditional cardiovascular risk factors. These results might implicate a role for type I IFN in modulating CV disease features in RA.